Comparative Removal of Chromium Cr(VI) from Wastewater by Sawdust and Activated Charcoal Derived from Acacia and Sheesham Wood - Ahmad, Shoaib; Haider, Bilal; Ahmad, Hafiz Bilal; Shafeeq, Amir (Chemical Engineering Journal Storage (CEJS), 2024)
This study investigates the removal of Chromium (VI) (Cr(VI)) ions from simulated wastewater using various adsorbents. The experiment employs unmodified sawdust (UMSD) and modified sawdust (MSD), along with activated charcoal (AC) derived from Acacia and Sheesham (Dalbergia Sissoo) wood. Batch experiments were conducted to assess the impact of several parameters including solution pH, adsorbent dosage (g/250 mL), contact time (minutes), and initial Cr(VI) concentration (ppm) on Cr(VI) adsorption at room temperature and pressure. SEM along with EDX as well as FTIR were used to analyze the adsorbent surface chemistry. The results revealed that AC exhibited the maximum Cr(VI) removal efficiency (90%) from the simulated wastewater due to its larger surface area as compared to UMSD (55%) and MSD (78%). Models of Freundlich and Langmuir isotherms were used to assess the adsorption process. Analysis of the model constants indicated that the Freundlich isotherm better described the experimental data for all adsorbents, as evidenced by the high correlation coefficient (R² = 0.99).